Diferenças no reconhecimento de osteoporose e da síndrome dos ovários policísticos entre os endocrinologistas e ginecologistas na cidade de Santa Maria – RS - Beber, Carla Costa (2017)
Chronic diseases such as systemic arterial hypertension, type 2 diabetes mellitus, osteoporosis and polycystic ovarian syndrome are prevalent in Brazil and are responsible not only for considerable morbidity and mortality in specific segments of the population, but also for high financial costs. Despite all their relevance, the diagnosis of these health problems in our country is not performed in an ideal way. As a consequence, there is a difficulty to act preventively in these pathologies, generating unwanted clinical complications. The difficulty of establishing diagnoses uniformly in common pathologies is not unique to our country. There are studies that demonstrate that the recognition of polycystic ovary syndrome is under-registered in developed countries such as Australia, as well as osteoporosis in China. At these sites, a variation in the identification of these pathologies has been demonstrated according to the physician's specialty. The objective of this study was to evaluate, through a questionnaire, the awareness regarding the diagnosis and management of polycystic ovarian syndrome and osteoporosis among the specialized physicians whom works in these areas (gynecologists and endocrinologists) in the city of Santa Maria, southern Brazil, where has a population of about 300,000 inhabitants. To improve this comparison, two other prevalent diseases (type 2 diabetes mellitus and systemic arterial hypertension) were included in the same questionnaire. A crosssectional study was carried out between July and August 2015 (Approval of CAAE 43401415.3.0000.5346). In total, 90% of endocrinologists and 75% of gynecologists out of a total of 97 physicians registered in the Regional Council of Medicine completed the questionnaire that was applied by a trained interviewer. No differences related to age, gender and time of work experience were observed among these specialists. In general, the responses of endocrinologists and gynecologists were consistent. Considering the questions about polycystic ovarian syndrome, the decision to include total testosterone, 17OHP, and prolactin was significantly higher in the group of endocrinologists than gynecologists. Regarding osteoporosis, the inclusion of the history of low-impact fractures in the diagnosis of osteoporosis was significantly more reported by gynecologists than endocrinologists. As expected, sequential identification of secondary causes of osteoporosis was more frequently performed by endocrinologists than gynecologists, who also identified a greater number of drug treatment options. To our knowledge, this is the first initiative to estimate differences in the recognition of polycystic ovarian syndrome and osteoporosis among gynecologists and endocrinologists using a medium-sized Brazilian city. It is believed that the information coming from this study will enable in the future the development of strategies and production of technical support materials directed to an improvement in the quality of the health care service.